Ukrainian educational policy on the culture of entrepreneurship in globalization, Europeanization, and glocalization - Olga Bakalinska; Olena Belianevych; Olena Honcharenko; Yuriy Pyvovar (Faculty of Social and Political Science, Universitas Airlangga, 2020)
Today, many factors contribute to the formation of educational policy in Ukraine as regards to the culture of entrepreneurial activity, in particular: globalization, Europeanization, and glocalization. Regarding the culture of entrepreneurial activity, critical stratification in the construction and understanding of business is the characteristic feature of contemporary understanding and is connected with the ‘Europeanization’ of entrepreneurial culture, etc. This article investigates general factors that influence educational policy in Ukraine, the formation of educational policy on entrepreneurship and the culture of the business. The foundation of studies in this article was the methodology of factor analysis. Diagnostic and forecasting methods made it possible to determine the prerequisites and trends for the formation of educational policy on the culture of entrepreneurship in Ukraine. The method of sociological observation helped to study employers’ representations about the status of higher education in the field of entrepreneurship culture. The methods of analysis and diagnosis were used to identify signs of modification of the Ukrainian educational policy on the culture of entrepreneurship in the context of globalization, Europeanization, and glocalization. As a result, it was possible to identify the general factors that influence the formation of educational policy in general and special ones that relate exclusively to entrepreneurial activity and the culture of an entrepreneur. The researchers claim that the pursuit to new progressive, and consistency and imitation are new trends, which must be balanced in the ethical code of the entrepreneur. It is claimed that ethical codes of entrepreneurs and ‘good practice’ are important components of Ukrainian business. At the same time, these instruments are at the formative stage; therefore, their development depends in many respects on educational policy, on the education of entrepreneurs in the spirit of good faith, the honest running of the business, and a responsible attitude to their activities.